Wintering and grazing yearling steers. The most efficient level of winter protein feeding for yearling steers wintered and grazed on bluestem pasture. - Baker, F.H.; Cox, R.F.; Smith, E.F.; Holland, L.A. (Kansas Agricultural Experiment Station, 2012)
Twenty good-quality Hereford yearling steers were used in this test. They were purchased as steer calves in the fall of 1953 from the Joyce Ranch near Carlsbad, N.M. During the summer of 1953 the steers were used in pasture management experiments. The current test was initiated November 10, 1954, and continued to April 6, 1955. To minimize differences due to pastures, the steers were moved monthly from pasture to pasture.
Keywords: Beef; Protein; Yearling steers; Pasture management; Gain